2006
DOI: 10.1111/j.1365-2265.2006.02630.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary tumour transforming gene (PTTG) expression correlates with the proliferative activity and recurrence status of pituitary adenomas: a clinical and immunohistochemical study

Abstract: PTTG is expressed in approximately 90% of pituitary tumours of different histotypes but with a high variability from one case to another. As expected, PTTG expression parallels that of Ki-67 and both are correlated to a more aggressive behaviour. However, a 2.9% Ki-67 cut-off proved to be the most reliable biological marker for predicting the recurrence potential of these tumours, when an adequate postsurgical follow-up is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 64 publications
(89 reference statements)
10
66
0
7
Order By: Relevance
“…PTTG and MMP9 were also up-regulated in the invasive tumors, as measured by qRT-PCR (data not shown), in keeping with previous findings (Turner et al 2000, Trouillas et al 2003, Filippella et al 2006, Gong et al 2008, Hussaini et al 2007, Wierinckx et al 2007. At the protein level, PTTG staining was stronger in invasive tissues and displayed a good correlation with that of MYO5A.…”
Section: Igfbp5supporting
confidence: 77%
See 1 more Smart Citation
“…PTTG and MMP9 were also up-regulated in the invasive tumors, as measured by qRT-PCR (data not shown), in keeping with previous findings (Turner et al 2000, Trouillas et al 2003, Filippella et al 2006, Gong et al 2008, Hussaini et al 2007, Wierinckx et al 2007. At the protein level, PTTG staining was stronger in invasive tissues and displayed a good correlation with that of MYO5A.…”
Section: Igfbp5supporting
confidence: 77%
“…In our series, Ki67 immunostaining was similar in invasive and non-invasive NFPAs, but the predictiveness of the Ki67 labeling index for aggressive behavior is greater in functioning pituitary adenomas (including prolactinomas) than in NFPAs (Gurlek et al 2007). Moreover, we have previously shown that the Ki67 labeling index is more reliable for predicting the recurrence of pituitary tumors (Filippella et al 2006).…”
Section: Igfbp5mentioning
confidence: 99%
“…PTTG1 was also identified as human securin, a critical regulator of sister chromatid separation in late stage mitosis (19,20). PTTG1 is expressed at very low or undetectable levels in most normal human tissues but is abundantly expressed in malignant cell lines and pituitary tumors (18,(21)(22)(23). However, the mechanisms by which PTTG1 contributes to tumor progression are not well understood.…”
mentioning
confidence: 99%
“…Oct-1 and hPTTG1 are concordantly expressed in endocrine tumors and colon cancers hPTTG1 is overexpressed in multiple human tumors including pituitary, breast, and colorectal tumors (Zhang et al 1999a, Solbach et al 2004, Filippella et al 2006. High Oct-1 protein expression was detected in gastric carcinomas (Almeida et al 2005).…”
Section: Zhou Et Al: Oct-1 Induces Hpttg1 Expressionmentioning
confidence: 99%
“…hPTTG1 abundance or loss of function (Jallepalli et al 2001, Wang et al 2001 both result in abnormal mitosis and chromosomal instability. In contrast to restricted normal tissue expression, hPTTG1 is upregulated in pituitary (Zhang et al 1999a, Filippella et al 2006, thyroid (Kim et al 2006), breast (Solbach et al 2004), esophageal (Shibata et al 2002), and colorectal tumors . The hPTTG1 overexpression correlates with tumor invasiveness, differentiation, tumor recurrence, and prognosis.…”
Section: Introductionmentioning
confidence: 99%